Reasons for indoor tanning use and the acceptability of alternatives: A qualitative study. (October 2021) - Lyons, Stephanie; Lorigan, Paul; Green, Adele C.; Ferguson, Ashley; Epton, Tracy
Abstract: Rationale: Using indoor tanning devices is associated with substantial health consequences, such as an increased risk of melanoma and other skin cancers. Many people including minors and some at high risk of skin cancer continue to use these devices. In the absence of effective restrictions on use, it is important that behaviour change interventions are designed to reduce indoor tanning. Objective: To explore reasons for use of indoor tanning devices and the acceptability of alternatives in adult users residing in North-West England. Methods: Participants were required to be current indoor tanners aged 18 years and above and were recruited online. Twenty-one participants took part in either a focus group or semi-structured interview. An inductive thematic analysis was conducted. Results: Six themes were identified: psychological benefits; improving physical health; denial of health risks; alternatives do not meet psychological needs; alternatives do not meet physical needs; and perceived side-effects. Participants used indoor tanning devices to improve their self-esteem and to prevent sun damage to their skin (by gaining a 'base tan'). Participants appeared to justify their usage by responding defensively to avoid accepting they were at risk, exaggerating the benefits of indoor tanning, and discounting alternatives to indoor tanning. Alternatives to indoor tanning were perceived as risky for health, inadequate to provide the desired aesthetic, and incapable of meeting their self-esteem needs. Conclusions: Interventions to reduce indoor tanning behaviour should increase sources of self-esteem other than appearance, increase media literacy and address defensive responses to information around indoor tanning and alternatives. Further research is needed to develop these interventions and assess their feasibility. Highlights: Using indoor tanning devices has health risks, but many people use them. Reasons for use include improving self-esteem and preventing sun damage. Users often exaggerate benefits, avoid risk acceptance and discount alternatives. Recommendations are made for interventions to reduce indoor tanning. Further research is needed to develop interventions and assess feasibility.